Investigation progress of geogrid-soil interaction using DEM. Issue 1 (1st October 2022) - Wang, Z; Ma, B; Yang, G; Ziegler, M
Abstract: The discrete element modeling, which has particular advantages of capturing detailed insights into the geogrid–soil interaction, provides a new perspective to study the geogrid reinforcement mechanism especially at a microscopic scale. To summarize the current investigation achievements, discrete element modeling of geogrid and soil as well as their interaction under different testing conditions were reviewed in this paper. The DEM investigations provide not only qualitative visualization of the geogrid–soil interaction but also quantitative response of the geogrid and its surrounding soil. Such investigation achievements provide researchers helpful hints for the design of geogrid reinforced soil structures.